Vil enden på ECB's opkøbsprogrammer få betydning for det danske realkreditmarked? - Christian Belling Sørensen; Magnus Stenfeldt Madsen (Danmarks Nationalbank, 2023)
The ECB has ended its net purchases of bonds. As a result, the ECB will no longer dampen volatility in the euro area bond markets to the same extent. This may lead to greater volatility in the Danish mortgage bond market. In recent years, banks have reduced their market-making capacity in the mortgage bond market, which may affect their ability to dampen increased volatility.
Keywords: 330; Rentenmarkt; Geldpolitik; Zentralbank; EU-Europäisch; Hypothek; Dänemark